High speed toughening-based ceramics grinding mechanism for quality and efficiency - Chongjun WU; Weicheng GUO; Zhouping WU; Kangmei LI; Beizhi LI; Steven Y. LIANG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2019)
Grinding has always been an effective precision machining method for hard-to-machine materials. The knowledge to grinding-induced material properties variation is important for promotion of grinding efficiency and quality, especially for High Speed Grinding (HSG) process. This paper is devoted to investigate the HSG induced material toughening mechanism with Smoothed Particle Hydrodynamics (SPH) simulation method and experimental analysis. In this paper, single grit SPH simulation work is conducted to reveal the indentation and scratching mechanism under different process parameters. Then grinding experiments with grinding force, microscopic topography and surface roughness are given to investigate the grinding wheel speed and chip thickness effects on grinding quality and efficiency. The results show that the SiC ceramic material gets toughened with extended plastic deformation under a higher indentation speed, which could directly avoid generating brittle fracture cracks after elastic deformation. Combined with the scratching results, it is believed that the transition of material removal mode occurred under different process parameters. Through the grinding experiments, it is suggested to grinding of SiC ceramics under a higher grinding wheel speed while moderate chip thickness to keep a desired materials removal rate.